Nonlinear Moment-Tensor Inversion of Repetitive Long-Periods Events Recorded at Pacaya Volcano, Guatemala - Lanza, Federica; Waite, Gregory P. (Frontiers in Earth Science, 2018)
Detailed models of low-frequency seismicity at volcanoes provide insights into conduit structure and dynamics of magmatic systems. We examine explosion-related long-period (LP) events from Pacaya volcano, Guatemala, that were recorded during a temporary installation of four broadband seismic stations from October 2013 to November 2013. The repetitive LP events are identified with the aid of infrasound measurements using a matched filter due to the high level of background tremor and the small magnitude of the recorded events. We derive a representative seismic signal from the phase-weighted stack of 8,587 of these similar events, and invert for a source moment tensor. To address the limitations posed by the limited number of stations of the local network, we employ a non-linear waveform inversion that uses a grid search for source type to obtain a quantitative measure of the source mechanism reliability. With only four stations, Pacaya represents a case of limited observational data, where a quantitative description of moment tensor uncertainty is needed before any interpretation is to be attempted. Results point to a shallow source mechanism somewhat like a tension crack, dipping ~ 40° to the east, consistent with the dominant E-W motion in the seismic records from stations west, north, and east of the source. The uncertainties determined from the non-linear inversion are not insignificant, but clearly constrain the mechanism to be a source dominated by isotropic components